Why Close a Bacterial Genome? The Plasmid of Alteromonas Macleodii HOT1A3 is a Vector for Inter-Specific Transfer of a Flexible Genomic Island - Fadeev, Eduard; De Pascale, Fabio; Vezzi, Alessandro; Hübner, Sariel; Aharonovich, Dikla; Sher, Daniel (Frontiers in Microbiology, 2016)
Genome sequencing is rapidly becoming a staple technique in environmental and clinical microbiology, yet computational challenges still remain, leading to many draft genomes which are typically fragmented into many contigs. We sequenced and completely assembled the genome of a marine heterotrophic bacterium, Alteromonas macleodii HOT1A3, and compared its full genome to several draft genomes obtained using different reference-based and de-novo methods. In general, the de-novo assemblies clearly outperformed the reference-based or hybrid ones, covering>99% of the genes and representing essentially all of the gene functions. However, only the fully closed genome (~4.5Mbp) allowed us to identify the presence of a large, 148 kbp plasmid, pAM1A3. While HOT1A3 belongs to Alteromonas macleodii, typically found in surface waters (“surface ecotype”), this plasmid consists of an almost complete flexible genomic island, containing many genes involved in metal resistance previously identified in the genomes of Alteromonas mediterranea (“deep ecotype”). Indeed, similar to A. mediterranea, A. macleodii HOT1A3 grows at concentrations of zinc, mercury and copper that are inhibitory for other A. macleodii strains. The presence of a plasmid encoding almost an entire flexible genomic island suggests that wholesale genomic exchange between heterotrophic marine bacteria belonging to related but ecologically different populations is not uncommon.